Identification of biallelic mutations in MCM3AP and comprehensive literature analysis - Liu, Chan; Xie, Qingfeng; Hu, Quan; Xiang, Bingwu; Zhao, Kaiyi; Chen, Xiang; Zheng, Feixia (Frontiers in Genetics, 2024)
Background: Minichromosome maintenance complex component 3 associated protein (MCM3AP) is a gene in which mutations can result in autosomal recessive peripheral neuropathy with or without impaired intellectual development. The MCM3AP genotype-phenotype correlation and prognosis remain unclear. The aim of this study was to explore the genotype-phenotype correlations pertaining toMethods: Whole-exome sequencing (WES) combined with copy number variation sequencing (CNV-seq) were performed on the genomic DNA isolated from four members of a Chinese family, and quantitative PCR and cDNA analyses were performed to examine the mutations. The retrospective study was conducted on 28 individuals with biallelic MCM3AP mutation-related diseases, including features such as mutations, motor development impairment, intellectual disability, weakness/atrophy, and cerebral magnetic resonance imaging abnormalities.Results: Sequencing identified novel compound heterozygous mutations in MCM3AP, namely, a paternal variant c.1_5426del (loss of exons 1-25) and a maternal splicing variant c.1858+3A>G.Functional studies revealed that the variant c.1858+3A>G resulted in the heterozygous deletion of exon 5, thereby affecting splicing functionality. Furthermore, the compound heterozygous mutation may affect the functionality of the protein domain. Retrospective analysis revealed different genotype-phenotype correlations for the pathogenic variants in biallelic MCM3AP: all individuals (100%) with mutations outside the Sac3 domain exhibited early-onset symptoms, motor developmental delays, and cognitive abnormalities, conversely, the proportions of individuals carrying mutations within the domain were 26.7% (motor delays) and 46.7% (cognitive abnormalities).Our findings further expand the genetic mutation spectrum of biallelic MCM3AP and highlight the genotype-phenotype associations. Additionally, we elaborate on the importance of rehabilitation intervention.